(3fTQ GdHfhO Ydi eQGbi GdSYhOs - (3YHO Gddg Hf EHQGgje GdYdhj GdTfbjWj, CHh eMeO,J (B1235 (3g` s ((3eMeO UGdM Hf ceGd GdOjf Hf CMeO JcQhQ s)
(3ChdgG (B:s
(3deG ef Gddg JYGdi HEJeGe GdfXe GdeSei (B: (3eQGbi GdSYhO Cdgefi Gddg GdZTJZGd HTQMg , aTQYJ ajg eTjQkG HdaX GdNTfi Edi GdceGd Hf CHj TQja fSjJ gPG GdTQM s
(3BNQgG (B:s
(3jYfi Cfg EPG LGA GdaGWei , hgh GdegOi GdefJXQ , dGjdRe JbdjO GdCQHYI , Hd jLhR def JPgH HePgH ef GdCQHYI Cf jfJbd dePgHI dCfg eLJgO hGdUMjM Cfg jTHg GdfHi Udi Gddg Ydjg hSde ai GdNdb HGdVe , dG ai GdNdb HGdaJM hGdMeO ddg Ydi EceGd gs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV YHGQJgG HGdMeQIs
(3cJHgG fGSNgG dCNjI ai Gddg eMeO Hf GdNTQi Hf GdSdGe Hf GdaGQhb s
(3TQM GdefXheI CdajI ai CUhd Gdabg s
(3fSNI eUMMIs
Keywords: (3CUhd Gdabgs